QAT'I AND ZANNI DEBATE FROM THE PERSPECTIVE OF QUR'ANIC STUDIES - Zarul Arifin; Maisyarah Rahmi Hasan; Abdurrahman Raden Aji Haqqi (QiST: Journal of Quran and Tafseer Studies, 2023)
In studying the Qur'an, two things absolutely must be considered, namely al-tsubut (source truth) and al-dalalah (meaning content). In the case of al-subutal-Qur'an, there is no difference of opinion among Muslims regarding the truth of the source (qath'itsubut) originating from Allah because it reaches the mutawatir of Muslims to ensure. All the verses of the Qur'an that Allah sent down through Jibril to the Prophet Muhammad. which are compiled in the Mushaf and read by Muslims around the world, which are agreed upon by Muslims, are no different and have changed since the beginning of their descent until now and in the future. Meanwhile, from a dalalah or editorial point of view, the contents of the Qur'anic verses related to law can be divided into qath'i and zanni verses. An in-depth study of al-Qur'an poetry shows that the existence of qathi'i and zanni poems is a characteristic of the al-Qur'an in explaining law (ahkam). This journal will discuss the Qath'i and zanni debates from the perspective of the Quran. The method used in the study of this paper is a literature review. Taking the main reference from the Quran, as well as the interpretation of the scholars. Hopefully this study will be useful to add to the body of knowledge, especially in the field of Quranic studies.